Desarrollo del proceso de atención de enfermería en paciente con ictericia por incompatibilidad o-a en el Hospital General Guasmo Sur. - Terán León, José Oswaldo (2020)
Jaundice in newborns is evidenced when the level of bilirubin in the blood exceeds the normal range reaching a figure of 5mg / dL. Bilirubin is a yellow compound resulting from the breakdown of red blood cells that reach their shelf life. Hemolytic disease of the newborn by ABO incompatibility (EHRN-ABO) is the most common of all blood group incompatibilities between the mother and the newborn. It occurs when the mother's blood group is O and that of the newborn is A or B. In hemolytic disease of the newborn: red blood cells are rapidly destroyed and anemia is caused by the presence of maternal antibodies directed against antigens present in the fetal red blood cells. The purpose of this case study is to develop a nursing care process in our newborn that enters the area due to presenting ABO incompatibility clinical picture. During his stay in the ward, our patient adjusts to nursing care such as: control of vital signs, daily weight, permanent eye mask placement, genital protection placement, changes of position every 3-4 hours to expose all areas of the body to light, among others. In addition to therapeutic treatment, all this allowed our newborn to evolve favorably and was discharged within four days of hospitalization in optimal clinical conditions.